Effect of high protein diet and probiotic Lactobacillus casei Shirota supplementation in aflatoxin B1-induced rats - Zainuddin, Nurul Adilah; Liew, Winnie Pui Pui; Sabran, Mohd Redzwan; Ismail, Amin (Hindawi, 2018)
Probiotic Lactobacillus casei Shirota (LcS) is a potential decontaminating agent of aflatoxin B1 (AFB1). However, few studies have investigated the influence of diet, especially a high protein (HP) diet, on the binding of AFB1 by probiotics. This research was conducted to determine the effect of HP diet on the ability of LcS to bind AFB1 and reduce aflatoxin M1 (AFM1) in AFB1-induced rats. Sprague Dawley rats were randomly divided into three groups: A (HP only), B (HP + 108 CFU LcS + 25 μg AFB1/kg BW), and C (HP + 25 μg AFB1/kg BW). Levels of AST and ALP were higher in all groups but other liver function’s biomarkers were in the normal range, and the liver’s histology showed no structural changes. The urea level of rats in group B (10.02 ± 0.73 mmol/l) was significantly lower () than that of rats in group A (10.82 ± 0.26 mmol/l). The presence of carcinoma in the small intestine and colon was more obvious in group C than in group B. Moreover, rats in group B had significantly () lower AFM1 concentration (0.39 ± 0.01 ng/ml) than rats in group C (5.22 ± 0.28 ng/ml). Through these findings, LcS supplementation with HP diet alleviated the adverse effects of AFB1 by preventing AFB1 absorption in the small intestine and reducing urinary AFM1.